Gene Expression Profiling for Postoperative Cognitive Dysfunction (POCD) Among High Risk Coronary Artery Bypass Graft (CABG) Patients - Noor Anisah Binti Abu Yazit (Universiti Sains Islam Malaysia, 2024)
Matric: 4192763(FPSK)